Efficacy of Social Security Allowances on Elderly Muslim of Rupakot Rural Municipality, Gandaki Province, Nepal - Silwal, Sudarshan; Adhikari, Bishow Bandhu (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This paper explores the efficacy of social security allowances (SSA) on elders of Muslim community in Rupakot Rural Municipality, Gandaki Province of Nepal through purposive selection. The study was conducted using both exploratory and descriptive research design. The data was primarily gathered using a five-point Likert scale and descriptively analyzed. The focus of the study was on Muslim elders aged 60 and above, out of 707 persons receiving allowances of different categories. Among the 27 senior citizens receiving SSA, one is widowed and one is partially disabled. The majority of SSA recipients are male, married, aged 70-75, engaged in agriculture, families with 2-4 members, and elders having ownership of assets. SSA program has shown to improve healthcare access, quality of life, lifestyle changes, poverty reduction, social respect, recognition, social participation, and self-dependency among elders in the Muslim community. Most elders use their SSA for essential daily living expenses, donation, supporting their own children and families, and contributing to educational and spiritual activities. Overall, SSA is seen as a financial relief rather than a burden within this community. This study suggests further research for exploring the long-term impact of SSA on diverse demographic groups in Nepal, to inform future policy decisions. Additionally, it recommends implementing educational awareness programs for elders to effectively manage SSA funds, and enhances policies to ensure timely and adequate disbursements of SSA.